Development and Clinical Translation of a Perioperative Nomogram Incorporating Free Fatty Acids to Predict Poor Outcome of Aneurysmal Subarachnoid Hemorrhage Following Endovascular Treatment - Wang, Yongyi; Xie, Yongfan; Wang, Houzhong; Zhang, Jifang; Li, Chuanfeng; Chen, Feng; Ren, Chengtao; Xu, Zhiming; Liu, Mingxing; Li, Luo; Li, Tong; Wang, Weimin (Frontiers in Neurology, 2021)
ABSTRACT Objective: A reliable prediction of clinical outcome is important for clinicians to set appropriate medical strategies in treating patients with aneurysmal subarachnoid hemorrhage(aSAH). In this study we aim to establish a perioperative nomogram involving serum lipid signatures for predicting poor outcomes at 3-month in aSAH patients following endovascular therapy. Methods: Data of aSAH patients receiving endovascular therapy were collected. Univariable and multivariable analysis were calculated to screen independent predictors related to unfavorable outcome defined by modified Rankin Scale (mFS) ≥3. A novel nomogram based on these significant features was conducted. Clinical application of this nomogram was assessed by Decision Curve Analysis (DCA) and clinical impact curve. Results: 213 patients were included (average age 58.9 years, 65.7% female), representing a poor 3-month outcome rate of 48.8%. Free fatty acid (FFA) levels on admission were efficient in predicting poor outcome compared to other contents in serum lipids. Univariable and multivariable analysis revealed advanced age (P=0.034), poor HH (OR=3.7, P<0.001) and mFS (OR=6.0, P<0.001), aneurysms in posterior circulation (OR=4.4, P=0.019) and higher FFA levels on admission (OR=3.1, P=0.021) were negative independent predictors of poor 3-month outcome. A novel nomogram composed of these significant features presented a concordance index of 0.831 while the practical benefit was validated by DCA and clinical impact curve. An online calculator based on R programming promoted the clinical application of this nomogram. Conclusion: Our nomogram involving age, HH grade, mFS, aneurysm location and serum FFA levels was sufficient to provide individualized prediction of 3-month poor outcome for each aSAH patients who underwent endovascular therapy.